PELAKSANAAN PROMOSI OBJEK WISATA BOOMBARA WATERPARK KABUPATEN KAMPAR - Desi Ratnasari; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to know how the implementation of promotion in Boombara Waterpark and respondents reaction about the implementation of promotion in Boombara Waterpark .This research is used descriptive quantitative methods. There were 100 sample of that people is taken for accidental sampling. The data collection techniques in this research used observation, interview, and quesionnaires. The likert scale was used to measure the intervals in quantitative data.This research used Fandi Tjiptono (2008:519) theory. This theory divides promotion mix into 5 categories: advertising, sales promotion, public relation, personal selling, direct mail.The result of the research shows that Boombara Waterpark has implemented promotion by using the promotion mix: Advertising, Sales Promotion, and Personal Selling. According to respondents, the implementation promotion in Boombara Waterpark is still needed to be improved.Keywords: promotion and promotion mix.